Dirac gaugions, R symmetry and the 125 GeV Higgs - Bertuzzo, Enrico; Frugiuele, Claudia; Gregoire, Thomas; Ponton, Eduardo [UNESP] (Springer, 2015)
We study a supersymmetric scenario with a quasi exact R-symmetry in light of the discovery of a Higgs resonance with a mass of 125 GeV. In such a framework, the additional adjoint superfields, needed to give Dirac masses to the gauginos, contribute both to the Higgs mass and to electroweak precision observables. We analyze the interplay between the two aspects, finding regions in parameter space in which the contributions to the precision observables are under control and a 125 GeV Higgs boson can be accommodated. We estimate the fine-tuning of the model finding regions of the parameter space still unexplored by the LHC with a fine-tuning considerably improved with respect to the minimal supersymmetric scenario. In particular, sizable non-holomorphic (non-supersoft) adjoints masses are required to reduce the fine-tuning.
Keywords: Higgs Physics; Beyond Standard Model; Supersymmetric Standard Model